Synthesis of material libraries using gas diffusion electrodes. Issue 23 (4th June 2020) - Prato M., Rafael A.; Van Vught, Vincent; Chayambuka, Kudakwashe; Pozo, Guillermo; Eggermont, Sam; Fransaer, Jan; Dominguez-Benetton, Xochitl
Abstract : Gas-diffusion electrocrystallization (GDEx), driven by oxygen reduction, produces libraries of nanostructures, including birnessites, cubic spinels, tetragonal spinels, and layered double hydroxides, with Co 2+ and Mn 2+ as metal precursors. Abstract : The future of energy relies on the advent of electrochemical energy production and storage. A key enabling factor is the effective synthesis of active materials, which, due to the global environmental circumstances and the growing demand, we must ensure are made sustainably. Thus, we unveil a rapid, sustainable, and scalable electrosynthesis route for a whole range of nanocrystalline materials with bright prospects for batteries, solar fuels and fuel cells, among others. For the proof of concept of the synthesis method, gas-diffusion electrocrystallization (GDEx), we synthesize manganese and cobalt oxides and hydroxides: Co-doped Na-birnessite, cubic/tetragonal spinels and layered double hydroxides (CoMn-LDH), owing to their current relevance. An oxygen depolarizing gas-diffusion electrode is used to fuel the oxidative synthesis at the electrochemical interface. Aside from the necessary metal precursors, all reagents are produced in situ with high efficiency. To elucidate the synthesis mechanism, a broad range of materials were produced under the same conditions. By changing the Co and Mn concentrations in the feed solution, the composition (Co/Mn stoichiometry), morphology (spinels vs. nanosheets), structure (tetragonal/cubic-spinel, birnessite, LDH), particle size (15–35 nm), crystallinity (polycrystalline particles vs. single-crystals), and phase purity were precisely tailored. A comprehensive library of nanostructures was built, wherein some materials exhibited outstanding catalytic properties for the oxygen evolution reaction, illustrating the significance of our strategy. To showcase the versatility of the method, we also prove the feasibility for sodium intercalation capacity in the materials, applicable to batteries. This work opens the door to a new systematic way of producing optimized and affordable materials for electrochemical energy applications and beyond.